(untitled) (Altre Modernità, 2011)
This article argues that 9/11 created a crisis of confidence amongst writers of American fiction by problematizing literary realism’s claims to verisimiltude and so undermining it as a plausible and credible mode of fiction. Surveying the post-9/11 debate over the merits and shortcomings of realism, this article suggests that the unlikely beneficiary of this crisis of confidence has been the contemporary nouveau roman, a mode of fiction that originates from within the literary traditions of continental Europe. The emergence of writers, publishers, reviewers, and readers attracted to the nouveau roman as a mode of literature in opposition to realism—and engaged in its production, evaluation, promotion, and dissemination—seems to signify a widespread dissatisfaction with the predominant American literary response to the crisis of 9/11. Providing a brief history of the emergence of this post-9/11 institutional support for the nouveau roman, this article contends that the nouveau roman requires a place in literary histories of post-9/11 American fiction even if it does not explicitly address the subject of 9/11 itself.